Investigating the Influence of Explicit Grammar Instruction for Indonesian EFL Students’ Academic Writing Skills - Rosmiaty Rosmiaty; Ratnawati Ratnawati; Yuriatson Yuriatson; Lusy Angraeny; Farah Muthiah Azani (ELT Worldwide: Journal of English Language Teaching, 2023)
Writing, as a fundamental skill in language acquisition, is intrinsically linked with grammar. For English as a Foreign Language (EFL) learners, especially those from linguistically diverse backgrounds like Indonesia, mastering grammar is both crucial and challenging. While the significance of grammar in writing is well-documented, there is a noticeable gap in research focusing on the specific needs and challenges of Indonesian EFL students. This study aimed to investigate the impact of explicit grammar instruction on the academic writing skills of Indonesian EFL students. It sought to identify specific grammatical challenges faced by these students, assess the effectiveness of targeted grammar instruction, and understand the strategies employed by learners to navigate these challenges. A qualitative research approach was employed, with purposive sampling selecting seven active grammar class attendees from the 6th semester of ABA UMI. Data collection instruments included observations, open interviews, writing tests, and documentation review. An interactive model of analysis was used for data interpretation. Preliminary results indicate that while all participants had foundational grammar knowledge, challenges persisted, especially with certain verb tenses. Explicit grammar instruction showed positive impacts on their writing skills, with real-world tasks enhancing the applicability of learned grammar. Participants also showcased diverse strategies to overcome grammatical challenges, underscoring the need for flexible instructional approaches. Explicit grammar instruction plays a pivotal role in enhancing the academic writing skills of Indonesian EFL students. Recognizing specific challenges and aligning instruction with real-world tasks can further optimize learning outcomes. This study offers valuable insights for educators, curriculum designers, and EFL learners, emphasizing the need for targeted, context-specific grammar instruction.